The Interconnected Health Initiative: A Smithsonian Framework to Extend One Health Research and Education - Comizzoli, Pierre; Pagenkopp Lohan, Katrina M.; Muletz-Wolz, Carly; Hassell, James; Coyle, Brian (Frontiers in Veterinary Science, 2021)
To better tackle diseases and sustain healthy ecosystems, One Health programs must efficiently bridge health in humans, domestic/livestock animals, wild animals and plants, agriculture/aquaculture, and the environment. The Smithsonian Institution proposes to address this by considering ‘health’ in a broad sense – the absence of undue pathogens and unnecessary stress for any organisms as well as access to good living conditions in safe environments. It also plans to fully integrate existing cultural, social, and educational components into health research on humans, animals, plants, or ecosystems. The objectives of this perspective article are to (1) propose an innovative framework to support an interconnected approach to health and (2) provide examples fostering impactful collaborations on Interconnected Health research and education. Based on the core strengths of the Smithsonian (multidisciplinary research, outreach and education programs, libraries/ archives, and collections) and central institutional support, this framework has the potential to enhance existing health-related projects, address new needs and situations (e.g. response to pandemics), provide invaluable resources to inform policy and decision makers, and educate all audiences globally.